Effect of flooding the salt pans in the Ria de Aveiro - Picado, A. (2009)
The Ria de Aveiro, a mesotidal lagoon located on the Northwestern Portuguese coast, is characterized by large areas of intertidal flats and a web of narrow channels. The lagoon has a large area of mostly abandoned salt pans, whose progressive degradation is caused by the lack of maintenance and by the strong currents which erode their protective walls. The shallow water model ELCIRC was implemented and calibrated for the Ria de Aveiro in order to study its hydrodynamics, with special emphasis on the effect of the destruction of the salt pans protective walls. The calibration was performed by adjusting the bottom friction coefficient, through the comparison between measured and computed time series of surface water elevations at several stations within the lagoon. Harmonic analyses of these data were performed in order to evaluate the models accuracy. An assessment of root mean square errors and skill showed that a good calibration was achieved. Once calibrated, ELCIRC was used to characterize the hydrodynamics of the entire lagoon and the channels around the salt pans under different scenarios (present athymetry and a projection of the bathymetry resulting from the walls destruction). An extreme destruction of the salt pan walls would result in a significant increase of the inundation area in Ria de Aveiro, as well as in changes of the global and local hydrodynamic regimes. In summary, this study reveals how the increase of the flooded area in estuarine lagoons can affect tidal propagation, including the increase of tidal currents, tidal prism and tidal asymmetry. The long-term implications of the salt pans inundation are discussed based on the results.